Genomic Insights Into Red Squirrels in Scotland Reveal Loss of Heterozygosity Associated With Extreme Founder Effects - Melissa M. Marr; Emily Humble; Peter W. W. Lurz; Liam A. Wilson; Elspeth Milne; Katie M. Beckmann; Jeffrey Schoenebeck; Uva‐Yu‐Yan Fung; Andrew C. Kitchener; Kenny Kortland; Colin Edwards; Rob Ogden (Evolutionary Applications)
ABSTRACT Remnant populations of endangered species often have complex demographic histories associated with human impact. This can present challenges for conservation as populations modified by human activity may require bespoke management. The Eurasian red squirrel, Sciurus vulgaris (L., 1758), is endangered in the UK. Scotland represents a key stronghold, but Scottish populations have been subjected to intense anthropogenic influence, including widespread extirpations, reintroductions and competition from an invasive species. This study examined the genetic legacy of these events through low coverage whole‐genome resequencing of 106 red squirrels. Previously undetected patterns of population structure and gene flow were uncovered. One offshore island, four mainland Scottish populations, and a key east‐coast migration corridor were observed. An abrupt historical population bottleneck, related to extreme founder effects, has led to a severe and prolonged depression in genome‐wide heterozygosity, which is amongst the lowest reported for any species. Current designated red squirrel conservation stronghold locations do not encompass all existing diversity. These findings highlight the genetic legacies of past anthropogenic influence on long‐term diversity in endangered taxa. Continuing management interventions and regular genetic monitoring are recommended to safeguard and improve future diversity.